Stimulated Immune Response by TruCulture® Whole Blood Assay in Patients With European Lyme Neuroborreliosis: A Prospective Cohort Study - Ørbæk, Mathilde; Gynthersen, Rosa Maja Møhring; Mens, Helene; Stenør, Christian; Wiese, Lothar; Brandt, Christian; Ostrowski, Sisse Rye; Nielsen, Susanne Dam; Lebech, Anne-Mette (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Borrelia burgdorferi sensu lato complex (B. burgdorferi) can cause a variety of clinical manifestations including Lyme neuroborreliosis. Following the tick-borne transmission, B. burgdorferi initially evade immune responses, later symptomatic infection is associated with occurrence of specific antibody responses. We hypothesized that B. burgdorferi induce immune hyporesponsiveness or immune suppression and aimed to investigate patients with Lyme neuroborreliosis ability to respond to immune stimulation. Methods An observational cohort study investigating the stimulated immune response by standardized whole blood assay (TruCulture®) in adult patients with Lyme neuroborreliosis included at time of diagnosis from 01.09.2018-31.07.2020. Reference intervals were based on a 5-95% range of cytokine concentrations from healthy individuals (n = 32). Patients with Lyme neuroborreliosis and references were compared using Mann-Whitney U test. Heatmaps of cytokine responses were generated using the webtool Clustvis. Results In total, 22 patients with Lyme neuroborreliosis (19 definite, 3 probable) were included. In the unstimulated samples, the concentrations of cytokines in patients with Lyme neuroborreliosis were comparable with references, except interferon (IFN)-α, interleukin (IL)-17A, IL-1β and IL-8, which were all significantly below the references. Patients with Lyme neuroborreliosis had similar concentrations of most cytokines in all stimulations compared with references. IFN-α, IFN-γ, IL-12 and IL-17A were lower than references in multiple stimulations. Conclusion In this exploratory cohort study, we found lower or similar concentrations of circulating cytokines in blood from patients with Lyme neuroborreliosis at time of diagnosis compared with references. The stimulated cytokine release in blood from patients with Lyme neuroborreliosis was in general slightly lower than in the references. Specific patterns of low IL-12 and IFN-γ indicated low Th1-response and low concentrations of IL-17A did not support a strong Th17 response. Our results suggest that patients with Lyme neuroborreliosis elicit a slightly suppressed or impaired immune response for the investigated stimulations, however, whether the response normalizes remains unanswered.